Kali Linux, an ethical hacker's cookbook practical recipes that combine strategies, attacks, and tools for advanced penetration testing - Sharma, Himanshu (Packt Publishing, 2019)
With the current rate of hacking, it is very important to pentest your environment in order to ensure advanced-level security. This book is packed with practical recipes that will quickly get you started with Kali Linux (version 2018.4/2019) as per your requirements and help you move on to core functionalities.